Dengue Hemorrhagic Fever Complicated with Spontaneous Rupture of the Spleen among Patients with Thalassemia and G6PD Deficiency: A Case Report - Ungthammakhun, Chutchawan; Chueansuwan, Worawong; Changpradub, Dhitiwat (Archives of Clinical and Medical Case Reports, 2021)
Dengue infection is endemic in Thailand and Southeast Asia and thalassemia is highly prevalent in this area too. The clinical spectrums of dengue fever range widely, and many complications can occur. Spontaneous splenic rupture is a very rare complication in dengue fever. Here, we report a case of dengue fever complicated with spontaneous splenic rupture in a 22-year-old man with thalassemia presenting acute febrile illness and left upper quadrant pain. Computerized tomography of the upper abdomen with contrast revealed diffuse enlarged size of spleen with focal active contrast extravasation at the spleen surrounded with hematoma, and generalized hemoperitoneum. The patients were treated with exploratory laparotomy and blood transfusion. The outcome depended on early diagnosis and management.